Realizing the Distinctive University : Vision and Values, Strategy and Culture - Roche, Mark William (Book collections on Project MUSE., 2017)
"In Realizing the Distinctive University: Vision and Values, Strategy and Culture, Mark Roche changes the terms of the debate about American higher education. A former dean of the College of Arts and Letters at the University of Notre Dame, Roche argues for the importance of an institutional vision, not simply a brand, and while he extols the value of entrepreneurship, he defines it in contrast to the corporate drive toward commercialization and demands for business management models. Using the history of the German university to assess the need for, and implementation of, distinctive visions at American colleges and universities, Roche's own vision benefits from his deep connection to both systems as well as his experience in the trenches working to realize the special mission of an American Catholic university. Roche makes a significant contribution by delineating means for moving such an institution from vision to implementation. Roche provides a road map to creating a superb arts and sciences college within a major research university and offers a rich analysis of five principles that have shaped the modern American university: flexibility, competition, incentives, accountability, and community. He notes the challenges and problems that surface with these categories and includes ample illustration of both best practices and personal missteps. The book makes clear that even a compelling intellectual vision must always be linked to its embodiment in rhetoric, support structures, and community. Throughout this unique and appealing contribution to the literature on higher education, Roche avoids polemic and remains optimistic about the ways in which a faculty member serving in administration can make a positive difference. Realizing the Distinctive University is a must read for academic administrators, faculty members interested in the inner workings of the university, and graduate students and scholars of higher education"--